Northview Elementary School: an iterative participatory process in schoolyard planning & design - Addo-Atuah, Kweku (Kansas State University, 2012)
There is currently a dearth of planning literature concerning participatory processes relative to children, particularly in the planning and design of schoolyard or playground spaces. Through a local, place-based, participatory approach emphasizing local knowledge and active listening, this master's report seeks to confirm the value of children in the planning and design of a schoolyard space. The study took place at the Northview Elementary School in Manhattan, KS comprising students as primary stakeholders, teachers/administrative staff as secondary stakeholders and parents as tertiary stakeholders. Additionally, the study employed Piaget’s and Vygotsky’s childhood cognitive development theories and five operational play categories in guiding the development of a learning landscape design aimed at supporting and maximizing cognitive development, physical activity and recreation. The report concludes with a set of five (5) recommendations designed to equip prospective researchers in undertaking participatory processes within school settings. The implication of this study is that sustained stakeholder engagement during planning and design processes of schoolyards will result in spaces reflective of the target audience.
Keywords: Landscapes of learning; Participatory design; Childhood cognitive development; Play categories; Landscape Architecture (0390); Urban Planning (0999)